Demographic and Regional Trends of Smoking among Thai Females from 1986 to 2014 (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Smoking is a major public health burden causing substantial morbidity and mortality. The aim of the study was to assess the prevalences and demographic trends of smoking among Thai females. Methods Data from Thailand’s National Statistics Office for 1986 to 2014 were used. Multiple logistic regression was implemented to identify the prevalences and trends of female smoking by region (Bangkok, Central, Northeast, North, and South) and area (Rural and Urban). Results: The overall prevalence of smoking was 3.4% among females aged 15 years and above in 2014. Gradually decreasing trends of smoking were observed from 1991 to 2007. Afterwards, the trends of smoking was found higher in 2011 to 2014 among aged 15-39 years. Furthermore, there were substantial differences in female smoking in different regions and areas. Of those, the Northern Thailand and rural areas had the highest prevalence of smokers. Conclusion: Smoking among Thai females in the past 20 years had a decreasing trend, but it can be seen that since 2007 the trend of smoking had shown an increasing trend and a variation among the regions. This imply that, tobacco control policies are important and in need particularly for young females, living in rural areas and Northern provinces.